Foodborne Microbial Pathogens Mechanisms and Pathogenesis - Bhunia, Arun K. (Food Science Text Series,, 2018)
This book primarily covers the general description of foodborne pathogens and their mechanisms of pathogenesis, control and prevention, and detection strategies, with easy-to-comprehend illustrations. The book is an essential resource for food microbiology graduate or undergraduate students, microbiology professionals, and academicians involved in food microbiology, food safety, and food defense-related research or teaching. This new edition covers the significant progress that has been made since 2008 in understanding the pathogenic mechanism of some common foodborne pathogens, and the host-pathogen interaction. Foodborne and food-associated zoonotic pathogens, responsible for high rates of mortality and morbidity, are discussed in detail. Chapters on foodborne viruses, parasites, molds and mycotoxins, and fish and shellfish are expanded. Additionally, chapters on opportunistic and emerging foodborne pathogens including Nipah virus, Ebola virus, Aeromonas hydrophila, Brucella abortus, Clostridium difficile, Cronobacter sakazakii, and Plesiomonas shigelloides have been added. The second edition contains more line drawings, color photographs, and hand-drawn illustrations.